UNderstanding uptake of Immunisations in TravellIng aNd Gypsy communities (UNITING): protocol for an exploratory, qualitative study. Issue 6 (8th June 2015) - Jackson, Cath; Bedford, Helen; Condon, Louise; Crocker, Annie; Emslie, Carol; Dyson, Lisa; Gallagher, Bridget; Kerr, Susan; Lewis, Helen J; Mytton, Julie; Redsell, Sarah A; Schicker, Frieda; et al.
Abstract : Introduction: Gypsies, Travellers and Roma (referred to here as Travellers) experience significantly poorer health and have shorter life expectancy than the general population. They are also less likely to access health services including immunisation. To improve immunisation rates, we need to understand what helps and hinders individuals in these communities in taking up immunisations. This study has two aims: (1) Investigate the barriers and facilitators to acceptability and uptake of immunisations among six Traveller communities in the UK; (2) Identify potential interventions to increase uptake in these Traveller communities. Methods and analysis: A three-phase qualitative study with six Traveller communities. PHASE 1: In each community, we will explore up to 45 Travellers' views about the influences on their immunisation behaviours and ideas for improving uptake in their community. PHASE 2: In each community, we will investigate 6–8 service providers' perspectives on barriers and facilitators to childhood and adult immunisations for Traveller communities with whom they work, and ideas to improve uptake. Interview data will be analysed using the Framework approach. PHASE 3: The findings will be discussed and interventions prioritised in six workshops, each with 10–12 phase 1 and 3–4 phase 2 participants. Ethics and dissemination: This research received approval from NRES Committee Yorkshire and The Humber-Leeds East (Ref. 13/YH/02). It will produce (1) findings on the barriers and facilitators to uptake of immunisations in six Traveller communities; (2) a prioritised list of potentially feasible and acceptable interventions for increasing uptake in these communities; and (3) methodological development in undertaking research with diverse Traveller communities. The study has the potential to inform new ways of delivering services to ensure high immunisation uptake. Findings will be disseminated to participants, relevant UK organisations with responsibility for the implementation of immunisation policy and Traveller health/welfare; and submitted for publication in academic journals. Trial registration number: ISRCTN20019630.